2015
DOI: 10.1159/000371796
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Islet Hormones in Human Adult Pancreatic Ducts

Abstract: Background/Aims: The source of insulin-secreting cells from adult duct system is attractive, but its clinical practice remains poorly understood. Here, we aimed at identifying the distribution of secreted hormone reactive cells in adult ducts. Methods: Consecutive pancreatic slices from nondiabetic subjects were subjected to immunohistochemistry and immunofluorescence to screen islet hormones (insulin; glucagon, Glu; somatostatin, Som; pancreatic polypeptide, PP) and exocrine biomarkers (cytokeratin 19, CK19; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Previous research found that tissues with high Ptf1α expression may differentiate into pancreatic acinar cells in pancreatic development [28]. CK19 is a marker of pancreatic exocrine cells and is expressed mainly in the duct [29]. Neuro D and Pax6 are involved in the regulation of differentiation and maturation of pancreatic endocrine cells [30], and gene mutations of both are related to the pathogenesis of diabetes mellitus [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that tissues with high Ptf1α expression may differentiate into pancreatic acinar cells in pancreatic development [28]. CK19 is a marker of pancreatic exocrine cells and is expressed mainly in the duct [29]. Neuro D and Pax6 are involved in the regulation of differentiation and maturation of pancreatic endocrine cells [30], and gene mutations of both are related to the pathogenesis of diabetes mellitus [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that allicin has anti-inflammatory and anti-thrombotic activities, and serves as an alternative antioxidant (Ariga & Seki, 2006;Chung, 2006;Li et al, 2015aLi et al, , 2015b. Based on the advantages conferred by allicin, we propose a possible hypothesis that allicin may retard the APAP-induced acute liver damage via attenuating intrahepatic inflammatory stress.…”
Section: Introductionmentioning
confidence: 93%
“…Overall, these experimental protocols were performed according to the manufacturer's manual (Boster, Wuhan, China) and previous descriptions (Li et al, , 2015b. The liver sections were dewaxed and rehydrated via stepwise concentrations of ethanol and xylene, respectively.…”
Section: Immunohistochemical Stainsmentioning
confidence: 99%
“…More interestingly, our previous human studies show that islet hormone‐producing cells are found in adult pancreatic ductal sections. The insulin‐ immunoreactive cells predominantly localize in terminal ductal branches where the “buds” may retain potential capability for beta‐cell neogenesis . Although some promising evidence reveal differential pathways for beta cells to regenerate, the molecular mechanism responsible for beta‐cell transdifferentiation from pancreatic ducts is not yet completely known.…”
Section: Introductionmentioning
confidence: 99%